Development of a poly(urethane-malonic-esteramide) coating from corn oil and carbon nanotubes for corrosion resistant applications. Issue 2 (17th February 2021) - Alam, Manawwer; Alandis, Naser M.; Alam, Javed; Ahmad, Naushad; Alam, Mohammad Asif
Abstract: Poly(urethane-malonic-esteramide) (PUMEA), a novel resin synthesized from corn oil-based fatty amide, malonic acid, and isophorone diisocynate, was modified by introducing different amounts of multi-walled carbon nanotubes (MWCNTs) into the polymer matrix and cured at room temperature. The chemical structure and surface morphology were characterized by Fourier-transform infrared spectroscopy, nuclear magnetic resonance, and field emission scanning electron microscopy, and thermal analysis was carried out by thermogravimetric analysis and differential scanning calorimetry. The PUMEA/MWCNTs composites were coated on mild steel panel and cured at room temperature. Hydrophobicity and physico-mechanical properties of the coatings were extracted by measuring contact angle, scratch and pencil hardness, bending, cross-hatch adhesion, impact, and gloss. The corrosion resistance was proved measuring the potentiodynamic polarization and electrochemical impedance of a PUMEA-coated mild steel panel immersed in a 3.5 wt% NaCl solution for 40 days. Thermal studies revealed that the PUMEA coating can be safely used up to 250 °C.